2021
DOI: 10.3390/polym13081211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sanding and Plasma Treatment of 3D-Printed Parts on Bonding to Wood with PVAc Adhesive

Abstract: Additive manufacturing is becoming increasingly important for manufacturing end products, not just prototyping. However, the size of 3D-printed products is limited due to available printer sizes and other technological limitations. For example, making furniture from 3D-printed parts and wooden elements requires adequate adhesive joints. Since materials for 3D printing usually do not bond very well with adhesives designed for woodworking, they require special surface preparation to improve adhesion. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Comparable gains for plasma-treated PLA bonded to wood with a PVAc adhesive (0.55-3.72 MPa) were reported by Kariž at al. [40]. On the other hand, Mandolfino et al [41] observed increases of between 52.5% and 386.6% in lap-shear tests performed on a plasma-treated polypropylene film-epoxy adhesive.…”
Section: Effect Of Plasma Treatment On the Performance Of Adhesive Jointsmentioning
confidence: 97%
“…Comparable gains for plasma-treated PLA bonded to wood with a PVAc adhesive (0.55-3.72 MPa) were reported by Kariž at al. [40]. On the other hand, Mandolfino et al [41] observed increases of between 52.5% and 386.6% in lap-shear tests performed on a plasma-treated polypropylene film-epoxy adhesive.…”
Section: Effect Of Plasma Treatment On the Performance Of Adhesive Jointsmentioning
confidence: 97%
“…Among the three treatment regimes, the combination treatment of plasma and sanding produced superior outcomes with respect to improving adhesion strength. Microscopic visualization of thus-treated surfaces showed the development of significant roughness after sanding, with some of this topography lost when the surface was subsequently exposed to plasma-induced ion bombardment [ 91 ].…”
Section: Plasma For Modifying Mechanical Properties Of Polymer Compositesmentioning
confidence: 99%
“… ( a , b ) Plasma device used for the surface treatment of 3D-printed samples on a CNC positioning system (top left image) with a gliding arc plasma jet ( a ), and sample for testing the bond shear strength ( b ). Reproduced from Kariž et al (2018) [ 91 ] under conditions of the CC BY license. ( c , d ) Representation of the crack path in ABS-interleaved hybrid composites ( c ) with untreated ABS ( d ) with plasma-treated ABS.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations